2008
DOI: 10.2143/ac.63.4.2033050
|View full text |Cite
|
Sign up to set email alerts
|

Value of BNP and tumour marker CA125 in patients with heart failure

Abstract: CA125 and BNP are markedly elevated in heart failure and closely reflect heart function. They are better markers in evaluating the efficiency of short-term therapy. Detecting BNP combined with CA125 may be more valuable than only detecting BNP or CA125 for diagnosing HF and evaluating the efficiency of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…Compared to those with CA 125 ≤ 5 U/ml, patients with CA 125 > 35 U/ml had higher serum levels of NT-proBNP and worse echocardiographic and haemodynamic parameters at baseline. In all 5 Cox models we constructed, CA125 > 35 U/ml was associated with an over 2-fold increased risk of 1-year clinical worsening, which was similar to the results seen in heart failure ( 32 , 33 ). Furthermore, ROC analysis showed that CA 125 provided additional predictive value in addition to the established PH biomarker NT-proBNP ( 18 ).…”
Section: Discussionsupporting
confidence: 65%
“…Compared to those with CA 125 ≤ 5 U/ml, patients with CA 125 > 35 U/ml had higher serum levels of NT-proBNP and worse echocardiographic and haemodynamic parameters at baseline. In all 5 Cox models we constructed, CA125 > 35 U/ml was associated with an over 2-fold increased risk of 1-year clinical worsening, which was similar to the results seen in heart failure ( 32 , 33 ). Furthermore, ROC analysis showed that CA 125 provided additional predictive value in addition to the established PH biomarker NT-proBNP ( 18 ).…”
Section: Discussionsupporting
confidence: 65%
“…The heterojunctions on the interface could provide an internal electric field to improve the surface reaction electrodynamics and facilitate electron/ion transport. 36,37 Successively, the pore size distributions of OMC-g-MXene heterostructure and etched MXene are comprehensively investigated by nitrogen adsorption−desorption isothermal curves (Figure S4). With the modification of OMC, the specific surface areas of OMC-g-MXene heterostructure is calculated to be 202.36 m 2 g −1 , which is much larger than that of densely packed MXene (17.52 m 2 g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The predictive value for all-cause mortality up to 6-months after index HF hospitalization had also been demonstrated by the same study group [22]. On the other hand, there also seems to be a moderate correlation between CA-125 and brain natriuretic peptide (BNP) level, the most commonly used biomarker reflecting degree of excessive ventricular wall stress, hemodynamics or ventricular filling abnormalities in left-sided HF [23,24]. Interestingly, though both markers had been reported to rise in acute heart failure, combination of them in clinical use may further improve risk stratification at follow up [23,25].…”
Section: Brief Introductionmentioning
confidence: 82%